2016
DOI: 10.3892/ijo.2016.3420
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol induces ATM/p53-mediated death receptor and mitochondrial apoptosis in human umbilical vein endothelial cells

Abstract: Abstract. Kaempferol is a member of the flavonoid compounds found in vegetables and fruits. It is shown to exhibit biological impact and anticancer activity, but no report exists on the angiogenic effect of kaempferol and induction of cell apoptosis in vitro. In this study, we investigated the role of kaempferol on anti-angiogenic property and the apoptotic mechanism of human umbilical vein endothelial cells (HUVECs). Our results demonstrated that kaempferol decreased HUVEC viability in a time-and concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…In addition, we also demonstrated that kaempferol suppressed U-2 OS cell metastasis through suppression of the ERK/p38/JNK and AP-1 signaling pathways (28). In an anti-angiogenic study, our earlier research indicated that kaempferol induced ROS-mediated p53/ATM-dependent apoptosis in human umbilical vein endothelial cells (HUVECs) (29). However, there is no available information regarding the possible major target and anti-angiogenic mechanism of kaempferol in endothelial cells.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, we also demonstrated that kaempferol suppressed U-2 OS cell metastasis through suppression of the ERK/p38/JNK and AP-1 signaling pathways (28). In an anti-angiogenic study, our earlier research indicated that kaempferol induced ROS-mediated p53/ATM-dependent apoptosis in human umbilical vein endothelial cells (HUVECs) (29). However, there is no available information regarding the possible major target and anti-angiogenic mechanism of kaempferol in endothelial cells.…”
Section: Introductionmentioning
confidence: 84%
“…In human umbilical vein endothelial cells (HUVECs), Lee et al () showed that kaempferol induces sub‐G1 phase cell population, activates the caspase signals such as caspase‐3, ‐8, and ‐9 and triggers apoptosis in a dose‐dependent manner. Additionally, it stimulates death receptor signals (death receptor 4 [DR4], Fas/CD95, and DR5) by enhancing the expressions of phosphorylated ataxia telangiectasia mutated (ATM) and phosphorylated p53 pathways (Lee et al, ).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…In human umbilical vein endothelial cells (HUVECs), Lee et al () showed that kaempferol induces sub‐G1 phase cell population, activates the caspase signals such as caspase‐3, ‐8, and ‐9 and triggers apoptosis in a dose‐dependent manner. Additionally, it stimulates death receptor signals (death receptor 4 [DR4], Fas/CD95, and DR5) by enhancing the expressions of phosphorylated ataxia telangiectasia mutated (ATM) and phosphorylated p53 pathways (Lee et al, ). In a similar fashion, research by Liao and colleagues revealed that kaempferol displays anticancer activity against different human cancer cell lines, such as the human stomach carcinoma (SGC‐7901), human breast carcinoma (MCF‐7), human lung carcinoma (A549), and human cervical carcinoma (Liao et al, ).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…In response to stress, p53 acts as a transcriptional factor that regulates the expression of downstream target genes involved in the cell cycle, apoptosis, DNA damage and senescence [27,28]. A correlation has been identified between p53 and the death receptor [29,30], which suggests a significant role of p53 in death receptor-mediated cell death. Metastasis is the main cause of cancer death, and the epithelial-to-mesenchymal transition (EMT) is a crucial process for metastasis [31,32].…”
Section: Introductionmentioning
confidence: 99%